2012
DOI: 10.1128/jcm.05853-11
|View full text |Cite
|
Sign up to set email alerts
|

Novel Real-Time Simultaneous Amplification and Testing Method To Accurately and Rapidly Detect Mycobacterium tuberculosis Complex

Abstract: The aim of this study was to establish and evaluate a simultaneous amplification and testing method for detection of the Mycobacterium tuberculosis complex (SAT-TB assay) in clinical specimens by using isothermal RNA amplification and real-time fluorescence detection. In the SAT-TB assay, a 170-bp M. tuberculosis 16S rRNA fragment is reverse transcribed to DNA by use of Moloney murine leukemia virus (M-MLV) reverse transcriptase, using specific primers incorporating the T7 promoter sequence, and undergoes succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
22
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 38 publications
2
22
1
Order By: Relevance
“…Simultaneous Amplification and Testing (SAT) is one of the molecular biological detection methods used by the tuberculosis laboratory in China in recent years. It is mainly used to detect MTB in sputum to assist diagnosis [4][5][6][7]. However, SAT has rarely been used to test EPTB specimens and therefore, its sensitivity and specificity for EPTB diagnosis are still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous Amplification and Testing (SAT) is one of the molecular biological detection methods used by the tuberculosis laboratory in China in recent years. It is mainly used to detect MTB in sputum to assist diagnosis [4][5][6][7]. However, SAT has rarely been used to test EPTB specimens and therefore, its sensitivity and specificity for EPTB diagnosis are still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the SAT-TB assay is intended for point-of-care testing for TB [ 10 ]. Recent researches showed that sensitivity of the SAT-TB assay for the diagnosis of PTB with sputum samples was from 39.2 to 93% [ 11 , 12 ]. In patients with sputum-scarce, the sensitivity of the SAT-TB test using bronchial alveolar lavage fluid (BALF) specimens was 50.75% [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is fast, simple and has good reproducibility [ 8 ]. Previous studies of the SAT-TB assay that focused on its accuracy with sputum samples demonstrated that its overall sensitivity for the diagnosis of PTB was 67.7% (range 39.2% to 93%) [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%